A mathematical and biological plausible model of decision-execution regulation in "Go/No-Go" tasks: Focusing on the fronto-striatal-thalamic pathway. (1st July 2017) - Baghdadi, Golnaz; Towhidkhah, Farzad; Rostami, Reza
Abstract: Discovering factors influencing the speed and accuracy of responses in tasks such as "Go/No-Go" is one of issues which have been raised in neurocognitive studies. Mathematical models are considered as tools to identify and to study decision making procedure from different aspects. In this paper, a mathematical model has been presented to show several factors can alter the output of decision making procedure before execution in a "Go/No-Go" task. The dynamic of this model has two stable fixed points, each of them corresponds to the "Press" and "Not-press" responses. This model that focuses on the fronto-striatal-thalamic direct and indirect pathways, receives planned decisions from frontal cortex and sends a regulated output to motor cortex for execution. The state-space analysis showed that several factors could affect the regulation procedure such as the input strength, noise value, initial condition, and the values of involved neurotransmitters. Some probable analytical reasons that may lead to changes in decision-execution regulation have been suggested as well. Bifurcation diagram analysis demonstrates that an optimal interaction between these factors can compensate the weaknesses of some others. It is predicted that abnormalities of response control in different brain disorders such as attention deficit hyperactivity disorder may be resolved by providing treatment techniques that target the regulation of the interaction. The model also suggests a possible justification to show why so many studies insist on the important role of dopamine in some brain disorders. Highlights: A mathematical model has been proposed to investigate decision-execution regulation in "Go/No-Go" tasks. The model focuses on the fronto-striatal-thalamic direct and indirect pathways. Simulations showed that the interaction of several effective factors can compensate the weakness of some others. The proposed model has a simple structure and is analytically tractable. A possible justification has been proposed to show why so many studies emphasis on the important role of dopamine.